Nicotinic α7 receptor activation selectively potentiates the function of NMDA receptors in glutamatergic terminals of the nucleus accumbens - Zappettini, Stefania; Grilli, Massimo; Olivero, Guendalina; Chen, Jiayang; Padolecchia, Cristina; Pittaluga, Anna; Tomé, Angelo R.; Cunha, Rodrigo A.; Marchi, Mario (Frontiers in Cellular Neuroscience, 2014)
We here provide functional and immunocytochemical evidence supporting the co-localization and functional interaction between nicotinic acetylcholine receptors (nAChRs) and N-methyl-D-aspartic acid receptors (NMDARs) in glutamatergic terminals of the nucleus accumbens (NAc). Immunocytochemical studies showed that a significant percentage of NAc terminals were glutamatergic and possessed GluN1 and α7-containing nAChR. A short-term pre-exposure of synaptosomes to nicotine (30 µM) or choline (1 mM) caused a significant potentiation of the 100 µM NMDA-evoked [3H]D-aspartate ([3H]D-Asp) outflow, which was prevented by α-bungarotoxin (100 nM). The pre-exposure to nicotine (100 µM) or choline (1 mM) also enhanced the NMDA-induced cytosolic free calcium levels, as measured by FURA-2 fluorescence imaging in individual NAc terminals, an effect also prevented by α-bungarotoxin. Pre-exposure to the α4-nAChR agonists 5IA85380 (10 nM) or RJR2429 (1 µM) did not modify NMDA-evoked ([3H]D-Asp) outflow and calcium transients. The NMDA-evoked ([3H]D-Asp) overflow was partially antagonized by the NMDAR antagonists MK801, D-AP5, 5,7-DCKA and R(-)CPP and unaffected by the GluN2B-NMDAR antagonists Ro256981 and ifenprodil. Notably, pre-treatment with choline increased GluN2A biotin-tagged proteins. In conclusion, our results show that the GluN2A-NMDA receptor function can be positively regulated in NAc terminals in response to a brief incubation with α7 but not α4 nAChRs agonists. This might be a general feature in different brain areas since a similar nAChR-mediated bolstering of NMDA-induced ([3H]D-Asp)overflow was also observed in hippocampal synaptosomes.